REMOVED: THE ARGUMENT STYLE OF RESEARCH ARTICLE DISCUSSIONS BY NON-NATIVE AUTHORS OF ENGLISH PUBLISHED IN INTERNATIONAL JOURNALS - Safnil Arsyad; Muhammad Zaim; Syahrul Ramadhan; Azhar Aziz Lubis (Journal of Applied Linguistics and Literature)
This article has been removed at the request of Professor Safnil Arsyad because the criteria for research output required by the research funder have yet to fulfill.